PENGENALAN LITERASI DIGITAL MATEMATIKA DARING BAGI WALI MURID SISWA KELAS VI SD NEGERI NGULAKAN - novy trisnani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
The application of online distance learning, which is carried out as an effort to prevent the spread of COVID-19, has greatly changed the role of parents at home. In an effort to help optimize children's learning processes, parents need to update their knowledge. The introduction of online mathematics digital literacy for the guardians of grade VI SD Negeri Ngulakan students is one of the efforts of the service to increase the knowledge, understanding and skills of the community in contributing to the environment around them. The PPM activity that has been carried out aims to increase the understanding and knowledge of the guardians of grade VI SD Negeri Ngulakan students about digital mathematics literacy. The dedication subjects were 18 students of grade VI students at SD Negeri Ngulakan as many as 18 people. From the results of the evaluation of the implementation of activities, it can be concluded that 1) is efficient and beneficial for the service participants; and 2) there is an increase in the participants' understanding and knowledge of digital mathematics literacy.